2015
DOI: 10.1136/bmjopen-2014-006429
|View full text |Cite
|
Sign up to set email alerts
|

Association between C reactive protein level and depressive symptoms in an elderly Korean population: Korean Social Life, Health and Aging Project

Abstract: ObjectiveThe relationship between inflammatory markers and depressive symptoms has been reported inconsistently. Moreover, there were only a few studies conducted in an Asian population. The purpose of this study was to examine the association between C reactive protein (CRP) and depressive symptoms in an elderly Korean population.Design, setting and participantsThis study used data from the Korean Social Life, Health and Aging Project Health Examination Cohort, which started in 2011. Among participants aged 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
17
3
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 34 publications
8
17
3
1
Order By: Relevance
“…Our findings are consistent with prior population-based studies that found no significant association between CRP and depression independent of BMI 12 15. Our findings also align with other studies that found no association between CRP and depression independent of other covariates related to depression, including antidepressant use and chronic illness 10 11 13 16 27…”
Section: Discussionsupporting
confidence: 92%
“…Our findings are consistent with prior population-based studies that found no significant association between CRP and depression independent of BMI 12 15. Our findings also align with other studies that found no association between CRP and depression independent of other covariates related to depression, including antidepressant use and chronic illness 10 11 13 16 27…”
Section: Discussionsupporting
confidence: 92%
“…However, most studies support a positive association between CRP and depressive symptoms both in men and women. [ 11 18 , 36 , 37 ] The mechanisms for the association between CRP and depressive symptoms are unclear, but various hypotheses have been develop to explain the relationship since CRP cannot cross the blood-brain barrier, and directly affect emotion regulating area in the brain. [ 21 ]…”
Section: Discussionmentioning
confidence: 99%
“…Similar evidences of the positive associations have been found in other studies. [ 11 18 ] However, contradictory evidences have been found in several studies. Chaiton et al, [ 19 ] Douglas et al, [ 20 ] and Au et al [ 21 ] found no significance association between CRP and depressive symptoms in the general population.…”
Section: Introductionmentioning
confidence: 99%
“…Even if not significantly different in the descriptive analyses, all of the above-mentioned variables were entered into the multiple logistic regression models for insomnia because we assumed that each variable could affect the other variables. Because marked sex differences were found in previous studies of our KSHAP sample, 24 25 26 27 28 we evaluated interaction effects between sex and all other variables by adding interaction terms into the regression model to maximize the number of independent variables.…”
Section: Methodsmentioning
confidence: 99%